Dynamic causal modeling reveals increased cerebellar- periaqueductal gray communication during fear extinction - Paci, Elena; Lumb, Bridget M.; Apps, Richard; Lawrenson, Charlotte L.; Moran, Rosalyn J. (Frontiers in Systems Neuroscience, 2023)
The extinction of fear memories is an important component in regulating defensive behaviours, contributing towards adaptive processes essential for survival. The cerebellar medial nucleus (MCN) has bidirectional connections with the ventrolateral periaqueductal grey (vlPAG) and is implicated in the regulation of multiple aspects of fear, such as conditioned fear learning and the expression of defensive motor outputs. However, it is unclear how communication between the MCN and vlPAG changes during conditioned fear extinction. We use dynamic causal models (DCMs) to infer effective connectivity between the MCN and vlPAG during auditory cue-conditioned fear retrieval and extinction in the rat. DCMs determine causal relationships between neuronal sources by using neurobiologically motivated models to reproduce the dynamics of postsynaptic potentials generated by synaptic connections within and between brain regions. Auditory event related potentials (ERPs) during the conditioned tone offset were recorded simultaneously from MCN and vlPAG and then modelled to identify changes in the strength of the synaptic inputs between these brain areas and the relationship to freezing behaviour across extinction trials. The DCMs were structured to model evoked responses to best represent conditioned tone offset ERPs and were adapted to represent PAG and cerebellar circuitry. With the use of Parametric Empirical Bayesian (PEB) analysis we found that the strength of the information flow, mediated through enhanced synaptic efficacy from MCN to vlPAG was inversely related to freezing during extinction, i.e., communication from MCN to vlPAG increased with extinction. The results are consistent with the cerebellum contributing to predictive processes that underpin fear extinction.